Die impak van metodologie op die verstaan van die Nuwe Testament - D. F. Tolmie (Acta Theologica)
During the previous century many new methods for interpreting the New Testament were developed. In this article it is asked if new methods always enable better insight into the New Testament. Although it is conceded that this is not always the case, it is argued that the correct application of new methods can indeed facilitate new insights into the New Testament. This is then illustrated by examples from the narratological analysis of the Fourth Gospel and the rhetorical analysis of the Letter to the Galatians.